PERAN WANITA PENGUSAHA DALAM KOLABORASI UNTUK MENINGKATKAN USAHA BISNIS DI SEKTOR PANGAN UMKM WILAYAH SURABAYA - Lilis Hidayatus Sugiarti; Titis Tatasari; Nur Festi Anadewi; Dimas Satrio Nugroho (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The aim of this research is to examine how female entrepreneurs can work together to improve business ventures in the MSME food industry in the Surabaya area. Qualitative analysis as well as in-depth interviews and documentation studies are the methodologies used. The findings of this research indicate that cooperation among women entrepreneurs can increase market accessibility, operational effectiveness and product innovation. Additionally, women entrepreneurs play an important role in expanding managerial skills and creating support systems. In addition to improving the status of women in the MSME food industry, this partnership encourages regional economic development.